Redes sociais : um estudo introdutório - Ferreira, André Luiz Bispo (2014)
This work aims to present a basic study of social networks and to show how some elements of this theory can be presented in classroom to illustrate and encourage the study of Graph Theory. To reach our goal, we developed some social network applications in State schools, through activities involving students and teachers as well as relationships between teachers and the educational institutions in which they work, activities which were developed using UCINET software.